A New Polymer-Coated Xenogeneic Extracellular Matrix to Prevent Postoperative Adhesion Readily Applicable in the Clinic - Kim, Kyung Hyun; Cho, Younghak; Choi, Yunyoung; Jeon, Seeun; Lee, Yun Jin; Seong, Hyejeong; Lee, Ji Yeoun (John Wiley & Sons Ltd., 2025)
Post-neurosurgical dura reconstruction is crucial for preventing CSF leakage and reducing infection risk. When primary closure is not possible, synthetic and semisynthetic dura substitutes are commonly used, but postoperative adhesions remain a major complication, particularly in reoperations for brain tumors and spinal surgeries. To address this, the use of initiated chemical vapor deposition (iCVD) is investigated to create a polymer-coated dura substitute that minimizes adhesions. iCVD, a dry, solvent-free technique, enables uniform polymer film deposition at low temperatures, ensuring biocompatibility and purity. A widely used dura substitute (Lyoplant) is coated with three biocompatible polymers (pHEMA, EGDMA, V4D4) and assessed cytotoxicity using fibroblasts. Adhesion levels are compared in vitro, and an intracranial adhesion model in mice is used for in vivo evaluation. All polymers exhibit minimal cytotoxicity, with pHEMA showing the least adhesion in vitro and selected for further testing. The uncoated dura causes severe adhesion to the cortex, leading to gross damage, whereas the pHEMA-coated dura prevents adhesion in 90% of cases. Histological analysis reveals inflammatory cell infiltration beneath the uncoated dura. These findings suggest that polymer-coated dura substitutes may reduce reoperation risks and improve patient recovery. Further studies are needed to assess long-term safety for clinical application.